Antibiotic resistance genes in bacteria: Occurrence, spread, and control - Jian, Zonghui; Zeng, Li; Xu, Taojie; Sun, Shuai; Yan, Shixiong; Yang, Lan; Huang, Ying; Jia, Junjing; Dou, Tengfei (Journal of basic microbiology, 2021)
The production and use of antibiotics are becoming increasingly common worldwide, and the problem of antibiotic resistance is increasing alarmingly. Drug‐resistant infections threaten human life and health and impose a heavy burden on the global economy. The origin and molecular basis of bacterial resistance is the presence of antibiotic resistance genes (ARGs). Investigations on ARGs mostly focus on the environments in which antibiotics are frequently used, such as hospitals and farms. This literature review summarizes the current knowledge of the occurrence of antibiotic‐resistant bacteria in nonclinical environments, such as air, aircraft wastewater, migratory bird feces, and sea areas in‐depth, which have rarely been involved in previous studies. Furthermore, the mechanism of action of plasmid and phage during horizontal gene transfer was analyzed, and the transmission mechanism of ARGs was summarized. This review highlights the new mechanisms that enhance antibiotic resistance and the evolutionary background of multidrug resistance; in addition, some promising points for controlling or reducing the occurrence and spread of antimicrobial resistance are also proposed.